"Titer of anti-HBs in health professions trainees: prevalence of antibody coverage in a University of Central Italy" - Luca Di Giampaolo; Erica Costantini; Marta Di Nicola; Annamaria Porreca; Gioele D'Amore; Luca Coppeta; Rocco Mangifesta (Taylor & Francis Group, 2022)
Objective This observational retrospective study aims at verifying hepatitis-B-virus (HBV) vaccination coverage in students vaccinated before and after 1992, in order to optimize health surveillance and vaccination recall. Methods Vaccination status was evaluated using the anti-HBs antibody titer (anti-HBs). Student t-test and the chi-square test were performed to identify the average age and the difference in antibody coverage between the two genders and in the two populations analyzed. Results Our study outlined a prevalence of 21.83% uncovered trainees among those vaccinated at age 12 and 45.03% among those vaccinated in neonatal age. Conclusion In conclusion, our data showed persistent protection against HBV infection in healthcare students.